The Functional Network Processing Acute Electrical Itch Stimuli in Humans - Mochizuki, Hideki; Hernandez, Loren E.; Yosipovitch, Gil; Sadato, Norihiro; Kakigi, Ryusuke (Frontiers in Physiology, 2019)
The posterior insula (pIns) is a major brain region that receives itch-related signals from the periphery and transfers these signals to broad areas in the brain. Previous brain imaging studies have successfully identified brain regions that respond to itch stimuli. However, it is still unknown which brain regions receive and process itch-related signals from the pIns. Addressing this question is important in identifying key functional networks that process itch. Thus, the present study investigated brain regions with significantly increased functional connectivity with the pIns during itch stimuli with 25 healthy subjects by using functional MRI. Electrical itch stimuli was applied to the left wrist. Similar to previous brain imaging studies, many cortical and subcortical areas were activated by itch stimuli. However, not all of these regions showed significant increments of functional connectivity with the pIns during itch stimuli. While the subjects perceived the itch sensation, functional connectivity was significantly increased between the right pIns and the supplementary motor area (SMA), pre-SMA, anterior midcingulate cortex (aMCC), anterior insula (aIns), secondary somatosensory cortex (SII) and basal ganglia (BG), suggesting that this is a key network in processing itch. In particular, intensity of functional connectivity between the pIns and BG was negatively correlated with itch rating. The functional pIns-BG pathway may play an important role in regulation of subjective itch sensation. This study first identified a key brain network to process itch.